2015
DOI: 10.1155/2015/217307
|View full text |Cite
|
Sign up to set email alerts
|

Kytococcus schroeteriBacteremia in a Patient with Hairy Cell Leukemia: A Case Report and Review of the Literature

Abstract: The Kytococcus genus formerly belonged to Micrococcus. The first report of a Kytococcus schroeteri infection was in 2002 in a patient diagnosed with endocarditis. We report a case of central line associated Kytococcus schroeteri bacteremia in a patient with underlying Hairy Cell Leukemia. Kytococcus schroeteri is an emerging infection in the neutropenic population and in patients with implanted artificial tissue. It is thought to be a commensal bacterium of the skin; however, attempts to culture the bacteria r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…4b, c ) are Dermabacter and Kytococcus, both of which have been reported to infect immunocompromised individuals 40 , 41 . The species Kytococcus schroeteri in particular has been found in multiple patients with myeloid malignancies 42 . Many other genera that contribute to discrimination among subtype (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4b, c ) are Dermabacter and Kytococcus, both of which have been reported to infect immunocompromised individuals 40 , 41 . The species Kytococcus schroeteri in particular has been found in multiple patients with myeloid malignancies 42 . Many other genera that contribute to discrimination among subtype (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review also identified 6 reported cases of Kytococcus pneumonia. Five of these were in conjunction with hematological malignancy (4 AML and 1 hairy cell leukemia) [1113, 17]. The sixth patient had no hematologic condition but was moderately immunocompromised by taking prednisone 20 mg daily for 2 years for management of refractory asthma [3].…”
Section: Discussionmentioning
confidence: 99%
“…Among the genera with the highest VI (Figure 4b,c) are Dermabacter and Kytococcus, both of which are known as opportunistic pathogens frequently affecting immunocompromised individuals 34,35 . The species Kytococcus schroeteri in particular has been found in multiple patients with myeloid malignancies 36 . Many other genera that contribute to discrimination among diagnoses (Figure 4b,c) are known causes of bacteremia, e.g., Staphylococcus, Streptomyces, Rothia, Gordonia, and Pandoraea, among others.…”
Section: Relationship Between Bacteriome and Clinical Characteristicsmentioning
confidence: 99%